Emerging Role of IL-10 in Hypertrophic Scars - Sun, Zi-Li; Feng, Yi; Zou, Ming-Li; Zhao, Bin-Hong; Liu, Si-Yu; Du, Yong; Yu, Shun; Yang, Min-Lie; Wu, Jun-Jie; Yuan, Zheng-Dong; Lv, Guo-Zhong; Zhang, Ji-Ru; et al. (Frontiers in Medicine, 2020)
Hypertrophic scars (HS) arise from traumatic or surgical injuries and the subsequent abnormal wound healing, which is characterized by continuous and histologically localized inflammation. Therefore, inhibiting local inflammation is an effective method of treating HS. Recent insight into the role of interleukin-10 (IL-10), an important anti-inflammatory cytokine, in fibrosis has increased our understanding of the pathophysiology of HS and has suggested new therapeutic targets. This review summarizes the recent progress in elucidating the role of IL-10 in the formation of HS and its therapeutic potential based on current research. This knowledge will enhance our understanding of the role of IL-10 in scar formation and shed new light on the regulation and potential treatment of HS.